Fine Arts Education in Rural Thailand: A Case Study of the Department of Art and Design, University of Phayao - et. al., Alex Wang, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Contemporary art is a global subculture typically associated with urban contexts. Infrastructure such as galleries, networks of brokers and collectors, auction houses, and museums, as well as an informed and engaged audience, are conventional hallmarks of a flourishing art scene. Educational institutions are also a crucial part of this infrastructure, not only in shaping the next generation of artists, but in presenting and promoting young artists’ work while simultaneously cultivating audiences. Thailand, with the exception of the Bangkok Greater Metropolitan Area, is devoid of any major urban centers. Numerous institutions of higher education have been established throughout the country, yet perhaps unsurprisingly, few of these institutions offer degrees in fine arts. However, as in the case of the University of Phayao (founded in 1996, and offering a BA in art and design beginning in 2012), more institutions are beginning to acknowledge the benefits of arts education regardless of an existing “arts infrastructure” to support them. Such benefits may include developing critical thinking, cultural awareness, and creative development. This research paper surveys the curriculum of the Department of Art and Design at the University of Phayao. Through interviews and site visits, the author examines the aims and objectives of these universities, their strategic plans for development, their impact on local communities, and how they envision the growth and development of their program.